2007
DOI: 10.1002/art.22647
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, immunologic, and genetic features of familial systemic sclerosis

Abstract: Objective. To examine whether the affected firstdegree relatives within multicase systemic sclerosis (SSc; scleroderma) families are concordant for autoantibody profile, disease type, and HLA class II haplotypes and whether clinical expression and serologic characteristics of familial SSc differ from those of sporadic SSc.Methods. Seven hundred ten SSc families from the Scleroderma Family Registry and DNA Repository (Scleroderma Registry) were examined, and 18 multicase families were identified. SSc cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…All patients with SSc fulfilled American College of Rheumatology (ACR) preliminary criteria for disease classification28 or had at least three of the five CREST (for ‘Calcinosis, Raynaud’s phenomenon, Eesophageal dysfunction, Sclerodactyly and Telangiectasias') features 29 30. Patients were not excluded if they had symptoms of myositis or Sjogren's syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…All patients with SSc fulfilled American College of Rheumatology (ACR) preliminary criteria for disease classification28 or had at least three of the five CREST (for ‘Calcinosis, Raynaud’s phenomenon, Eesophageal dysfunction, Sclerodactyly and Telangiectasias') features 29 30. Patients were not excluded if they had symptoms of myositis or Sjogren's syndrome.…”
Section: Methodsmentioning
confidence: 99%
“…This is supported by the higher familial relative risk of the disease itself or autoimmune diseases [4, 8], low disease concordance but high concordance of autoantibodies produced in monozygotic twins [5], and multi-case SSc families that are concordant for SSc-specific autoantibodies as well as human leukocyte antigen (HLA) haplotypes [9]. Twin studies have been performed in several autoimmune diseases.…”
Section: Genetic Involvementmentioning
confidence: 99%
“…Interestingly, twin-studies revealed a high concordance of autoantibody production in monozygotic twins (FeghaliBostwick et al 2003), familial relative risks in SSc patient Wrst-degree relatives is 13-fold higher than in the general population, and 15-fold higher in siblings (Arnett et al 2001), and multi-case SSc families are concordant for autoantibody production and HLA-haplotypes (Assassi et al 2007). Hence, considering all supporting evidence for the contribution of genetic factors to the disease, SSc was deWned as a complex disease in which genetic susceptibility J. E. Martín · L. Bossini-Castillo · J. Martín (&) Instituto de Parasitología y Biomedicina López-Neyra, IPBLN-CSIC, Consejo Superior de Investigaciones CientíWcas, Parque Tecnológico Ciencias de la Salud, Avenida del Conocimiento s/n 18100-Armilla, Granada, Spain e-mail: martin@ipb.csic.es and diVerent environmental triggers interact both in the pathogenesis and in the prognosis of the disease (Gabrielli et al 2009).…”
Section: Introductionmentioning
confidence: 96%